Bevacizumab (Avastin®) in cancer treatment: A review of 15 years of clinical experience and future outlook. (June 2020) - Garcia, Josep; Hurwitz, Herbert I.; Sandler, Alan B.; Miles, David; Coleman, Robert L; Deurloo, Regula; Chinot, Olivier L
Highlights: Bevacizumab (Avastin®), a VEGF-A targeting monoclonal antibody, was the first approved angiogenesis inhibitor. Approved in a range of solid tumor indications, bevacizumab is an important part of the standard of care in oncology. The recently identified immune modulatory roles of VEGF provide a powerful rationale for combination therapies. First clinical studies of the combination of bevacizumab with immune checkpoint inhibitors have shown efficacy. Abstract: When the VEGF-A-targeting monoclonal antibody bevacizumab (Avastin®) entered clinical practice more than 15 years ago, it was one of the first targeted therapies and the first approved angiogenesis inhibitor. Marking the beginning for a new line of anti-cancer treatments, bevacizumab remains the most extensively characterized anti-angiogenetic treatment. Initially approved for treatment of metastatic colorectal cancer in combination with chemotherapy, its indications now include metastatic breast cancer, non-small-cell lung cancer, glioblastoma, renal cell carcinoma, ovarian cancer and cervical cancer. This review provides an overview of the clinical experience and lessons learned since bevacizumab's initial approval, and highlights how this knowledge has led to the investigation of novel combination therapies. In the past 15 years, our understanding of VEGF's role in the tumor microenvironment has evolved. We now know that VEGF not only plays a major role in controlling blood vessel formation, but also modulates tumor-induced immunosuppression. These immunomodulatory properties of bevacizumab have opened up new perspectives for combination therapy approaches, which are being investigated in clinical trials. Specifically, the combination of bevacizumab with cancer immunotherapy has recently been approved in non-small-cell lung cancer and clinical benefit was also demonstrated for treatment of hepatocellular carcinoma. However, despite intense investigation, reliable and validated biomarkers that would enable a more personalized use of bevacizumab remain elusive. Overall, bevacizumab is expected to remain a key agent in cancer therapy, both due to its established efficacy in approved indications and its promise as a partner in novel targeted combination treatments.